A data integrity verification scheme in mobile cloud computing. (1st January 2017) - Lin, Chen; Shen, Zhidong; Chen, Qian; Sheldon, Frederick T.
Abstract: The provable data possession (PDP) scheme is vital to data-oriented mobile cloud computing security architecture. Without an efficient PDP scheme, users cannot verify whether the server retrieves original data before the data is being processed. One big issue of recent PDP verification schemes is that computation complexity and space overheads are very high. In this paper, we develop 2 comprehensive mobile provable data possession schemes (MPDP) using a hash tree data structure and a Boneh–Lynn–Shacham short signature scheme. Our MPDP schemes support data dynamics via verification outsourcing, blockless verification, stateless verification, and dynamic data operations. Experimental results show that these 2 MPDP schemes are highly accurate in the data verification process, and have a low data transmission cost. Highlights: The use of ternary Merkle hash tree instead of binary one will decrease the communication cost between TTP and CSP. The use of a trusted third party for bilinear pairing calculation is suitable for mobile environment. Support of dynamic data operations on file blocks, such as insert, delete and update.